Mustard (Brassica Juncea L.) Growth Hydroponically Using AB-Mix and Liquid Organic Fertilizer Tea Pulp - Trisnawati, Dinda Putri; Suparti, S (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Mustard greens are vegetables that have a high potential to be cultivated and contain nutrients. Hydroponics is an alternative to the cultivation of mustard plants. AB Mix and liquid organic fertilizer are nutrients to increase plant productivity. In addition, the content of tea pulp can help plant growth. This study was conducted to determine the effect of AB Mix concentration and tea pulp liquid organic fertilizer on mustard growth hydroponically. The study used a Complete Randomized Design in an experimental setting with four different AB Mix nutrient combinations treatments and tea pulp liquid organic fertilizer in the form of V0 (control), V1, V2, and V3. Each treatment is repeated four times. The results showed that the concentration of AB Mix and liquid organic fertilizer tea pulp affected the growth of mustard plant height, number of leaves, and wet weight of mustard plants. The greatest treatment on V2 has a plant height of 14 cm, lots of leaves 7 strands, and a wet weight of 5.8 g.